First re-factor the equation defining #h(x)# to have just one occurrence of #x#, then move the operations away from the term in #x# to leave it isolated.
#y = h(x) = 3 - (x+4)/(x-7)#
#=3-((x-7)+11)/(x-7)#
#=3-cancel(x-7)/cancel(x-7)-11/(x-7)#
#=3 - 1 - 11/(x-7)#
#=2-11/(x-7)#
Subtract #2# from both ends to get:
#y - 2 = -11/(x-7)#
Multiply both sides by #(x-7)# to get:
#(x-7)(y - 2) = -11#
Divide both sides by #(y-2)# to get:
#x -7 = -11/(y - 2)#
Add #7# to both sides to get:
#x = 7-11/(y-2)#
This defines #x# in terms of #y = h(x)#, so:
#h^-1(y) = 7 - 11/(y-2)#
with restriction #y != 2#